First report on the autochthonous gut microbiota of brown trout (Salmo trutta Linnaeus). (15th April 2014) - Al‐Hisnawi, Ali; Ringø, Einar; Davies, Simon J; Waines, Paul; Bradley, Graham; Merrifield, Daniel Lee
Abstract: A study was conducted to characterize the autochthonous gut microbiota present in the pyloric caeca (PC), anterior mucosa (AM) and posterior mucosa (PM) of brown trout ( Salmo trutta ). Total viable counts (TVC) bacterial populations were enumerated using tryptone soy agar, lactic acid bacteria (LAB) levels were enumerated on de Man, Rogosa & Sharpe agar and PCR‐DGGE was employed as a culture‐independent method to assess the total communities. No significant differences were observed between the different gut regions for TVC or LAB levels. 16S rRNA sequencing identified all LAB isolates as Carnobacterium maltaromaticum . In contrast, the TVC community was more diverse; Firmicutes and Bacteroidetes were present but all gut regions were dominated by Proteobacteria, accounting for 88.4–92.6% of the communities. Citrobacter freundii was the dominant species and accounted for 51.0–57.8% of the isolates. Complex bacterial communities were observed using PCR‐DGGE and a trend towards the reduction in the number of operational taxonomic units (OTUs), microbial richness and microbial diversity was observed from the PC to the PM. The similarity between regions was low (52–68%) and cluster analysis revealed that the communities grouped into two distinct clusters; one dominated by the PM samples and the other contained the AM and PC samples. OTUs from the DGGE were identified as members of the phyla Proteobacteria and Firmicutes. Many OTUs were detected in all gastrointestinal regions, however, some OTUs showed regional specialization. Further studies are required to elucidate the activity of these genera in situ and how their actions impact the host.